Constraints to the use of artificial insemination service and possible solutions - Mburu, J.; Ojango, Julie M.K.; Kariuki, K.; Baltenweck, Isabelle (International Livestock Research Institute, 2011)
The East Africa Dairy Development (EADD) project is aregional industry development program implemented by a consortium of partners led by Heifer International. It is currently being piloted in 18 sites in Kenya, 8 in Rwanda and 27 in Uganda. The overall goal of the project is to transform the lives of 179,000 families, or about 1 million people, by doubling household dairy income in 10 years through integrated interventions in dairy production, market access and knowledge application. This brief highlights key results of a baseline survey that was carried out with the objective of analyzing the level of preference for and use of artificial insemination (AI) in different project sites, and identifying constraints or problems hindering the optimal use of the service and possible solutions. Details are available in the baseline survey report No. 2.